Equidad de género en los medios de comunicación y su impacto en el ejercicio profesional en el Sector Santa Teresa, cantón Buena Fe Provincia de Los Ríos - Estacio Baque, Judy Nathaly (2020)
This research was carried out with the objective of determining the impact of the media on gender equity in professional practice, in the Santa Teresa sector, Buena Fe canton, Los Ríos province. According to our research objective, the methodology used qualitative and quantitative. Through a survey it was measured how the media impact on gender equity in professional practice. After this survey, it was concluded that the population believes that the media have a positive influence on the promotion of gender equity in terms of human rights. In the same way it was known that the medium that the population believes that places more emphasis on the promotion of gender equity in terms of human rights is television.